Simple Statistical Analysis of the Impact of Some Nonidealities in Downstream VDSL with Linear Precoding. (22nd September 2010) - Baldi, Marco; Chiaraluce, Franco; Garello, Roberto; Polano, Marco; Valentini, Marcello
Abstract : This paper considers a VDSL downstream system where crosstalk is compensated by linear precoding. Starting from a recently introduced mathematical model for FEXT channels, simple analytical methods are derived for evaluating the average bit rates achievable, taking into account three of the most important nonidealities. First, absolute and relative estimation errors in the crosstalk coefficients are discussed, and explicit formulas are obtained to express their impact. A simple approach is presented for computing the maximum line length where linear precoding overcomes the noncoordinate system. Then, the effect of out-of-domain crosstalk is analyzed. Finally, quantization errors in precoding coefficients are considered. We show that by the assumption of a midtread quantization law with different thresholds, a relatively small number of quantization bits is sufficient, thus reducing the implementation complexity. The presented formulas allow to quantify the impact of practical impairments and give a useful tool to design engineers and service providers to have a first estimation of the performance achievable in a specified scenario.